Workers' Health Risk Behaviors by State, Demographic Characteristics, and Health Insurance Status - Yi Huang, MD; Peggy A. Hannon, PhD, MPH; Barbara Williams, PhD; Jeffrey R. Harris, MD, MPH, MBA (Centers for Disease Control and Prevention, 2011)
IntroductionEmployers often lack data about their workers' health risk behaviors. We analyzed state-level prevalence data among workers for 4 common health risk behaviors: obesity, physical inactivity, smoking, and missed influenza vaccination (among workers older than 50 years).MethodsWe analyzed 2007 and 2008 Behavioral Risk Factor Surveillance System data, restricting the sample to employed respondents aged 18 to 64 years. We stratified health risk behavior prevalence by annual household income, educational attainment, health insurance status, and race/ethnicity.ResultsFor all 4 health risk behaviors, we found significant differences across states and significant disparities related to social determinants of health - income, education, and race/ethnicity. Among uninsured workers, prevalence of smoking was high and influenza vaccinations were lacking.ConclusionIn this national survey study, we found that workers' health risk behaviors vary substantially by state and by workers' socioeconomic status, insurance status, and race/ethnicity. Employers and workplace health promotion practitioners can use the prevalence tables presented in this article to inform their workplace health promotion programs.